Unlawful occupation of housing as a paradigmatic example of the feminization of poverty: a gender-based analysis - Palomino Jiménez, Cristina (My University, 2025)
From a criminological and a gender perspective, crimes committed by women are predominantly non-violent and often have an instrumental or functional nature, closely linked to the phenomenon of the feminization of poverty. This study examines the unlawful occupation of housing by women as a paradigmatic case, analysing the structural conditions that lead many women in vulnerable situations to irregularly occupy dwellings, as well as the legal and social consequences they face; specially the limitation of certain social benefits, such as public housing. In Spain, an analysis of unlawful housing occupation reveals that men and women commit this offense in equal measure, despite men generally engaging in criminal activity at a significantly higher rate. Over a ten-year period, the number of housing occupation offenses committed by men and women has been roughly equal, highlighting a well-documented structural issue: homelessness, like other forms of social inequality, disproportionately affects the most vulnerable groups. Furthermore, certain municipal regulations restrict access to public housing for individuals with records of offenses related to usurpation or damage to public property, exacerbating the structural barriers to achieving a dignified life. This phenomenon extends beyond Spain; it can also be seen in certain Western countries, such as in some US states or the United Kingdom. This study, therefore, analyses female delinquency using the example of women's housing problems and the crime of unlawful occupation of housing, emphasizing the impact of excessive bureaucratic control on access to social assistance and underscoring the need for more inclusive policies with a gender perspective.
Keywords: Usurpación - Andalucía; Marginación social; Mujeres - Situación económica; Gender perspective; Feminization of social exclusion; Female delinquency; Unlawful occupation of housing